2007
DOI: 10.1158/1055-9965.epi-06-1023
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and Its Receptor in Breast Cancer: Correlation with Steroid Receptors and Outcome

Abstract: Autocrine/paracrine erythropoietin (EPO) action, promoting cell survival and mediated by its receptor (EPOR) in various solid tumors, including breast carcinoma, questions about the prognostic and therapeutic interest of this system. The expression of EPO/EPOR is steroid dependent in some tissues; however, a clear relationship of EPO/EPOR and steroid receptors in breast cancer has not been established thus far. Recently, the field of steroid receptors has expanded, including rapid effects mediated by membrane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 62 publications
8
29
0
5
Order By: Relevance
“…In our study, we found EPO-R expression in 36.2% of cases, and Pelekanou et al showed that in 50 cases (82%) the tumor mass was positive for EPO-R, with staining being more intense at the growing edge of the tumor [31]. In our material we also evaluated the relationship between clinical features, such as histological grade of malignancy, tumor size or presence of lymph node metastases and expression of HIF-1α, and receptor for EPO, but no statistically significant correlations were demonstrated.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, we found EPO-R expression in 36.2% of cases, and Pelekanou et al showed that in 50 cases (82%) the tumor mass was positive for EPO-R, with staining being more intense at the growing edge of the tumor [31]. In our material we also evaluated the relationship between clinical features, such as histological grade of malignancy, tumor size or presence of lymph node metastases and expression of HIF-1α, and receptor for EPO, but no statistically significant correlations were demonstrated.…”
Section: Discussionsupporting
confidence: 67%
“…36). An inverse relationship between EpoR expression and disease-free and overall survival in breast cancer has been reported (37) and Epo may only have a negative effect in cancers that are positive for EpoR expression using immunohistochemistry (35). However, further studies are needed with more specific antibodies and greater sample numbers to determine the prognostic significance of EpoR expression on tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane androgen binding sites have been reported in a number of normal or malignant tissues and lesions. In particular, androgen sites have been detected in T lymphocytes (Benten et al, 1999), spermocytes and sperm (Walker, 2003), breast cancer (Pelekanou et al, 2007), prostate cancer , and colon cancer (Gu et al, 2009). In both breast and prostate, membrane-acting androgen have been reported to induce tumor regression alone (Hatzoglou et al, 2005) or in combination with cytoskeletal acting drugs (Kampa et al, 2006), suggesting a potential therapeutic role of membrane androgen agonists in breast and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%